Developmentalisme dan Institusionalisasi Budaya Lokal di Bengkulu Era Razie Jachya (1989–1994): Fondasi Historis Komodifikasi Budaya - Hasbi Arrizqi; Henderi Kusmidi (JOM, 2026)
This study examines the relationship between development and culture in Bengkulu Province during the leadership of Razie Jachya (1989–1994), focusing on how the New Order's developmentalist politics promoted the institutionalization of local culture, which later became the historical foundation for cultural commodification. Previous studies on regional development during the New Order have predominantly emphasized economic growth and administrative governance, while the relationship between development and the transformation of local culture has received relatively limited scholarly attention. This research aims to explain how development not only reshaped the social order but also transformed the position and function of culture in public life. Employing the historical method—including heuristics, source criticism, interpretation, and historiography—the study is analytically informed by Arturo Escobar’s theory of developmentalism and George Yúdice’s concept of culture as a resource. The findings reveal that development under Razie Jachya represented a form of developmentalism that expanded state intervention through the sectors of public health, social welfare, education, youth affairs, and culture. In the cultural sphere, policies such as the Tabot Festival, the establishment of the Bengkulu Museum, the development of cultural studios, cultural documentation programs, and the incorporation of local content into education demonstrate the institutionalization of local culture through state policies and institutional mechanisms. This process transformed culture from a communal practice into a developmental resource employed for regional identity formation, political legitimacy, and territorial promotion. The study concludes that although cultural commodification had not yet fully developed during the 1989–1994 period, the institutionalization of culture under Razie Jachya established the historical foundation that enabled the subsequent expansion of cultural commodification. These findings highlight the importance of positioning cultural communities as the primary actors in regional cultural governance to ensure that the utilization of culture for development remains aligned with the preservation of local cultural values.